PENYIDIKAN TINDAK PIDANA PENISTAAN AGAMA MELALUI MEDIA INTERNET OLEH RESERSE KRIMINAL KHUSUS KEPOLISIAN DAERAH RIAU - Suri, Aidil Fitri; ', Erdianto; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Cyber crime is one of the dark sides of technological advances that have a very wide negative impact on all areas of modern life today. Crime which is a crime of cyber crime is Illegal contents, that is evil by entering data or information to internet about something that is not true, unethical, and is considered to violate law or disturb public order. Based on data that writer get at Directorate of Criminal Investigation Special Police Region Riau, there is one form of crime cyber crime namely the Crime of Penusaan Religion through Internet Media, the crime of defamation of religion through internet media regulated in Article 28 paragraph (2) of Law Number 19 year 2016 about the change of Law Number 11 Year 2008 on Information and Electronic Transactions which reads: